Evaluation and Analysis of Mental Health Level of College Students With Financial Difficulties Under the Background of COVID-19 - Feng, Yongpeng; Zhang, Yunting (Frontiers in Psychology, 2021)
Under the background of COVID-19, the mental health of college students with financial difficulties deserves our attention. Conducted by questionnaires with SPSS for data analysis and integration, the study introduces the theory of resilience to measure the mental health status of students with financial difficulties and provides reference for improving the mental health level of this special group during the COVID-19.